PEMILIHAN CERPEN ANAK UNTUK BAHAN AJAR DI SEKOLAH DASAR SEBAGAI MEDIA PENANAMAN BUDI PEKERTI - Ade Husnul; Siti Hikmah (Jurnal Tuturan, 2012)
Actually kids short story which has clear reader’s segmentation, which  include children 7-12 years old. The special thing from kids short story  which is delivered is very familiar with children’s wolrd. Generally, kids short story in Indonesiatakes the theme about friendshis, games, and everything whch contain of moral education value, such as : help each ther is a positive thing, cheating is a negative thing, and obey parents, command is an obligation for children. Positive and negative thing in kids short story are explained clearly with the purpose to apply moral values clearly toward the children.  Most of kid short stories are written by adult. Therefore, there are many kids short stories which are awared or not by the writer, use language whch is not appropriate with the age and the competence of the children. Besides that, there are many short stories that contain of effort to buld good behaviour whch is delivered by teaching, even unsuitable with the psychological condition of the children. Those are that cause the mportance of choosing right teaching materials in teaching literature especially short story to the children. The actor or actress and event in the short stry can be the character who nspired the children. Through those actors, values of behaviour are delivered to the children as a reader of literature. Thus, the process to choose short story as a teaching material in the school  need the sensitivity of the teacher. hopefully the techer able to choose the right short story  for he chldren to be used as a teaching material in the classroom, that is literature teaching material which talk about children’s world with children language and with the characters who can appear the impression to the children that the character are themselves or their friends, not their parents or their teachers who impressed techng them. By the other words, short story which give moral education naturally to the children, go with flow without teaching impression. Besides that, teachers are hoped not only use the book as a reading resource, but also search the other teaching materials that more appropriate with the conditon of the children. Teaching material,especially short story, which found in text book, it shoud not be a holy book whch always followed because however the teacher who undrstand the condition of the children in the classroom. Thus, literature material in subject of indonesian language is hoped can be something which is exciting for the students and give the advantages in building their characters.